Promoting Inclusive Education: Enhancing the Quality and Addressing Challenges in Teaching Islamic Religious Education to Children with Special Needs - Salabi, Agus Salim (Institut Agama Islam Negeri Lhokseumawe, 2022)
The focus of this research is on the collaboration between teachers' roles and parental participation in creating effective learning for children with special needs through an inclusive curriculum. This study is a qualitative field research using a descriptive survey technique. Informants are comprised of school principals, teachers, and several staff members. Informant selection was done using data representatives technique. The results of the study show that (1) efforts by teachers in teaching children with special needs are carried out through understanding the needs of the child, adjusting the learning materials, creating structured lesson plans, utilizing technology, developing social and personal skills of the child, developing vocational skills, evaluating and revising the learning process, and (2) the development of the curriculum for children with special needs involves parental participation by improving communication, creating a conducive learning environment, assisting children with homework, encouraging creative learning activities, and building positive emotional relationships.